Effects of TiO2, Ag-TiO2, and Cu-TiO2 nanoparticles on mechanical and anticariogenic properties of conventional pit and fissure sealants - Sumaira Aziz; Rabia Javed; Anna Nowak; Saad Liaqat; Zia Ul Haq Khan; Naveed Ahmad; Mateusz Dulski; Krzysztof Matus; Pervaiz Ahmad; Nawshad Muhammad (Elsevier, 2023)
The objective of this study was to determine the effects of TiO2, Ag-TiO2, and Cu-TiO2 nanoparticles (NPs) addition on the mechanical and antibacterial properties of resin-based sealants. TiO2, Ag-TiO2, and Cu-TiO2 NPs were characterized with FTIR, Raman, SEM-EDX, TEM, XPS, and XRD, and evaluated for cytotoxicity study. After characterization, the nanoparticles were mixed with commercial pit and fissure sealants (PAFS) in ratios of 1 and 2%. A total of 7 groups were made, control group (PAFS only) and experimental groups (1%-2% TiO2, 1%-2% Ag-TiO2, and 1%-2% Cu-TiO2). ISO standards were adopted to prepare samples for mechanical properties, i.e., compressive strength (CS), flexural strength (FS), and Vickers hardness evaluation. Samples were tested against Streptococcus mutans through an agar well diffusion test. The CS, FS, and Vickers hardness were increased for the Cu-TiO2 group with respect to Ag-TiO2 but values were less compared to TiO2 groups. The highest flow rate was measured in the control group which was 8.16±0.06 mm and 9.17±0.1 mm after 3 and 10 mins respectively. In the agar well diffusion test, the control group showed no zone of inhibition, and the lowest zone of bacterial inhibition was found in PAFS with 1% TiO2 NPs group (13.3 ± 1.5 mm) while the highest was found in PAFS with 2% Ag-TiO2 NPs (21.8 ± 1.7 mm). Cu-doped TiO2 NPs showed more biocompatibility as compared to Ag-doped TiO2. The outcomes were statistically significant for all the mechanical tests and agar well diffusion antibacterial test as the p-value ≤0.05 while for the cytotoxicity test, the p-value >0.05. The TiO2 addition generally improved both the mechanical and antibacterial properties of pit and fissure sealant.